Isolated Bladder Exstrophy: A Rare Case - Rasouli, Ehsanullah; Wahdat, Abdullah; Nazari, Mohammad Jawid (New Visions in Medicine and Medical Science Vol. 10, 2024)
Exstrophy-Epispadias Complex (EEC) is a rare congenital malformation of the lower genitourinary tract, with a worldwide incidence of 1 per 46,000 live births. This case report presents a rare occurrence of bladder exstrophy variant in a one-day-old male newborn. The patient presented with Isolated bladder exstrophy and normal phallus with imperforated anus, congenital heart disease, and a left ectopic kidney. During palpation, protruding intestinal contents were identified, exerting pressure posteriorly on the exstrophied bladder. Surgical interventions included cut-back anoplasty, bilateral ureteral reimplantation, and primary bladder closure in a single operation, resulting in a successful outcome without complications. Three months of follow-up showed satisfactory surgical results. However, future continence levels should be monitored, and corrective surgery performed if necessary. Further research and case studies are warranted to enhance our understanding of this rare condition and optimize management strategies for affected individuals.